Leontiev and Napoleon III: Two Conservatism Tendencies of the Same Century - A. A. Krotov (Концепт: философия, религия, культура, 2024)
The subject of the study is the dispute between the Russian philosopher, K. Leontiev, and the French emperor, Napoleon III, regarding the meaning and orientation of historical events. The topicality of the study is determined by the importance of the problem of progress in the modern world and the need to take into account the entire range of previous approaches to it. The novelty is defined by the absence of works in which a comparison of the two analyzed approaches would be presented. The article uses the following methods: hermeneutic, phenomenological, and comparative historical. The policy of Napoleon III is characterized in the artistic works of Leontiev as well as in the works in philosophical and publicistic genres. In the novel Odysseus Polychroniades, the Second French Empire appears as a mechanical structure devoid of a spiritual core. In the autobiographical work Egyptian pigeon, the emperor appears as a usurper. In his philosophical and political writings, Leontiev focuses on the theory of cultural types. Napoleon III's France in this context serves as an illustration of the period of secondary mixing and simplification in the lives of civilizations. But its history is also important to Leontiev as a kind of reference point in the historical coordinate system, which allows us to compare the Western path with the fate of Russia. The Russian thinker strongly emphasized the connection between the history of his country and Byzantine principles. He saw its future in their preservation and support. Leontiev considered France, which rushed along the path of liberal egalitarianism, a decaying state characterized by decomposition and loss of originality and religiosity, as well as by the transition from complexity to a more primitive organization. Napoleon III, on the contrary, considered France the vanguard of civilization, and the principle of nationalities proclaimed by him was seen as the only reliable basis for international politics. Although Leontiev and Napoleon III do not have the same interpretations of progress, in their understanding of the general meaning of history and the laws of civilizational development both considered it necessary to introduce conservative elements into public life. The forecasts of the Russian philosopher regarding the future give more reason to name him (rather than the emperor) a prophet.